MENJELAJAHI PERAN MUSIK DALAM MENURUNKAN STRES TERHADAP MAHASISWA UNIVERSITAS BINA SARANA INFORMATIKA ANGKATAN TAHUN 2021 - Abid Nabil Erlangga; Fandi Dika Irwanda, Luqman Nur Hakim, Nur Alif Alfino Saputra, Raihan Mahesa Abdul Rapi, Yogi Saputr (CV. ADIBA ASIHA AMIRA, 2024)
Students are often faced with various pressures and challenges which result in stress. Students often look for activities that can provide positive energy, one of which is activities related to music. This makes music a part of students' daily activities. Several researchers say that music is believed to affect students' physical and mental health. This research aims to analyze the role of music in reducing stress in Bina Sarana Informatics University students class of 2021. The results show that out of 82 students, there are 77 (93.9%) students who like to listen to music when they experience stress while doing assignments. It can be concluded that music plays a very important role in reducing stress for students in carrying out various activities on campus because music can have a relaxing and calming effect on those who listen to it.